Revamp Aplikasi Teman Bumil Lebih Interaktif Dengan Pendekatan Agile - Tofid; Eddy Julianto; Yulius Harjoseputro (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Teman Bumil (Friends of Millennial Mother) is application is an application developed to help pregnant women which contains some information from running a pregnancy program to monitoring the growth and development of pregnant women. This application was first released in 2017 with the number of active users currently having a stickiness rate of ± 13% per month which in this case is proven by the interview method conducted by researchers. However, this number is still considered unstable because it is only around 13%, where the target of stickiness rate is ± 15% for the month. Several improvements have been made by adding health charts, online classes, new media features, and registration using a new method, namely OTP (One Time Password). the results of this change have not been as expected. Therefore, in this study, we propose Revamp or an update using the Flutter framework which produces an application that can be used by both the iOS and Android platforms or also called a hybrid so that it is more interactive and according to user needs. In addition, this study also uses the Agile development method with the Scrumban model, which is a combination of Scrum and Kanban. The results of this research are in the form of a Teman Bumil application that has been revamped and has also been tested for the application developed and has received a good response from users based on randomly distributed questionnaires.